A Seamless Ubiquitous Telehealthcare Tunnel - Cheng, Po-Hsun (MDPI, 2013)
Mobile handheld devices are rapidly using to implement healthcare services around the World. Fundamentally, these services utilize telemedicine technologies. A disconnection of a mobile telemedicine system usually results in an interruption, which is embarrassing, and reconnection is necessary during the communication session. In this study, the Stream Control Transmission Protocol (SCTP) is adopted to build a stable session tunnel to guarantee seamless switching among heterogeneous wireless communication standards, such as Wi-Fi and 3G. This arrangement means that the telemedicine devices will not be limited by a fixed wireless connection and can switch to a better wireless channel if necessary. The tunnel can transmit plain text, binary data, and video streams. According to the evaluation of the proposed software-based SCTP-Tunnel middleware shown, the performance is lower than anticipated and is slightly slower than a fixed connection. However, the transmission throughput is still acceptable for healthcare professionals in a healthcare enterprise or home care site. It is necessary to build more heterogeneous wireless protocols into the proposed tunnel-switching scheme to support all possible communication protocols. In addition, SCTP is another good choice for promoting communication in telemedicine and healthcare fields.